Kinerja Manajerial Mempengaruhi Akuntabilitas Pengelolan Dana Otsus, Komitmen Organisasi Dan Kejelasan Sasaran Anggaran - Eliana Eliana; Farah Ivana; T.Muhammad Jumeil; Armia Armia (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The study aims to analyze the accountability of decision funds, the commitment of the organization and the clarity of budget targets towards managerial performance at the Aceh Financial Management Agency both simultaneously and partially.The sample of this research is a staff member of the Aceh Financial Management Agency with a total of 29 staff members using census techniques. To test each item on each variable, a validity and reliability test of the instrument has been carried out. The results of the analysis show that simultaneously there is an influence on the accountability of otsus funds, organizational commitment and clarity of budget targets on managerial performance. The result of the F test is obtained a number Fcalculus > Ftable or (22,814>2,73) and the test signifies that the p value of 0,000<p is set to 0.05 which means significant. Partially variable decision fund accountability, organizational commitment and budget objective clarity influence managerial performance. The determination coefficient value of 73.2% indicates that the ability of the independent variable (the accountability of the otsus fund, the organic commitment and the clarity of budget targets) in explaining dependent variables (management performance) and the rest are other variables not described in this study.